VISIT PROFILES AND TOURISM DESTINATION THRESHOLDS USING POLYNOMIAL AND MALTHUSIAN - Dalengkade, Mario Nikolaus; Kaseside, Meidy; Maatoke, Cornelia Dolfina; Boleu, Fiktor Imanuel; Buka, Oktosea; Loklomin, Samsul Bahri; Mangimbulude, Jubhar Christian (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Kumo, Kupa-Kupa, Pitu, and Luari beaches are tourist destinations that are always crowded with local and foreign tourists. This becomes interesting, because recently the problem of human population density in an area has become a hot topic for study. Using the polynomial method, it resulted in 6th order with R2 0.950 (Kumo), 0.868 (Kupa-Kupa), 0.799 (Pitu), and 0.399 (Luari) representing the distribution of visits. The highest levels of visits occurred in the twelfth, fifth, fourth, and sixth months, respectively. The analysis by applying the logistics function shows the highest level of visits throughout 2018 which are Kumo 283.95 tourists, Kupa-Kupa 342.12 tourists, Pitu 81.77 tourists and, Luari 1088.35 tourists. Based on the threshold analysis, the threshold value shows 255.56 tourists (Kumo), 297.08 tourists (Kupa-Kupa), 65.58 tourists (Pitu), and 836.42 tourists (Luari). The results of this study inform the level of tourist visits exceeding the threshold value in four tourist destinations. Given that the four tourist destinations carry the concept of ecology as a selling point, the manager needs to reorganize the level of tourist visits. Excess levels of tourist arrivals can have a negative impact on the comfort and sustainability of tourist destinations